KAJIAN PENERAPAN PRINSIP DESAIN UNIVERSAL PADA MUSEUM STUDI KASUS: MUSEUM GEOLOGI BANDUNG - Indriastjario, Indriastjario; Naima, Sani Puspaning; Wijayanti, Wijayanti (architecture department, Engineering faculty, Universitas Diponegoro, 2018)
Bandung is one of the main tourist destinations in Indonesia. The city has many pull factors for visitors. Since 2014, the city of Bandung has done many improvements in various places such as making thematic parks, improving it's town square, etc. This affects the development of tourism in Bandung. So far, design concept of tourism in Indonesia has not been design for disabled people, or people with special needs even though tourism is a right for everyone. Friendly tourism for people with disabilities will be able to provide facilities and accessibility for everyone with different needs and characteristics. This study aims to find out to what extent tourism management can provide facilities and accessibilities for disabled people and the extent to which the application of universal design principles is applied to the building. The inspection method used is an applied research using quantitative descriptive approach to collect data. Data collected is analyzed by using guidelines from No.30/PRT/M/2006 under regulations by Ministry of Public Works, and Smithsonian Guidelines for Accessible Exhibition Design..